مستوى الصلابة النفسية لادى ممرضي الصحة العمومية الذين لهم خبرة في مصلحة كورونادراسة ميدانية بمستشفى 240سريربولاية الأغواط - نسرين طيفوري; قرينات بن شهرة (My University, 2021)
The study aimed to know the level of psychological toughness in its three dimensions (commitment, control and challenge), among public health users (nurses) and to detect gender differences in the level of psychological hardness, as well as the differences between those with professional experience (more than 5 years) and less than five years (5 years). ), where the study sample amounted to (40) male and female nurses working in a 240-bed hospital in the state of Laghouat The study adopted a questionnaire of psychological hardness prepared by Imad Mukhaimer and adapted by (Bashir Maamaria) to the Algerian environment. The validity and reliability of the tool were verified, and after data collection, they were processed by statistical methods using the statistical package for social sciences. The results of the study concluded that the study sample has a high level of hardness There are also differences between the sexes in the level of hardness in favor of females, and there are differences between those with professional experience (more than 5 years) and less than five (5) years in favor of more than five years